2023
DOI: 10.1042/ebc20220165
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ion beam deposition plus low-energy electron holography as a tool for imaging individual biomolecules

Abstract: Inline low-energy electron holography (LEEH) in conjunction with sample preparation by electrospray ion beam deposition (ES-IBD) has recently emerged as a promising method for the sub-nanometre-scale single-molecule imaging of biomolecules. The single-molecule nature of the LEEH measurement allows for the mapping of the molecules’ conformational space and thus for the imaging of structurally variable biomolecules, thereby providing valuable complementary information to well-established biomolecular structure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…Already, direct combination of native MS and various analysis methods revealed retention of globular shape and biological activity of proteins and viruses ( 28 31 ). More recently, improved workflows using cryo-EM, negative-stain transmission electron microscopy (TEM), or low-energy electron holography have demonstrated that protein complexes retain their overall shape at a resolution in the nanometer range ( 31 – 36 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Already, direct combination of native MS and various analysis methods revealed retention of globular shape and biological activity of proteins and viruses ( 28 31 ). More recently, improved workflows using cryo-EM, negative-stain transmission electron microscopy (TEM), or low-energy electron holography have demonstrated that protein complexes retain their overall shape at a resolution in the nanometer range ( 31 – 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…Already, direct combination of native MS and various analysis methods revealed retention of globular shape and biological activity of proteins and viruses ( 28 31 ). More recently, improved workflows using cryo-EM, negative-stain transmission electron microscopy (TEM), or low-energy electron holography have demonstrated that protein complexes retain their overall shape at a resolution in the nanometer range ( 31 – 36 ). However, in the absence of a method that provides structures of proteins at the level of side-chain resolution, the extent to which the solution structure is retained in the native ESIBD process has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive works for optimal collection and subsequent characterization of ionic species from low kinetic energies (soft landing) or reactive landing and with controlled kinetic energies have been reported. ,,, ISL has been used to gain structural information on biological molecules (i.e., large proteins and viruses) due to its ability to largely preserve biological activity and conformations. , For example, in biomedical applications such as the synthesis and coating of particles and proteins used for disease diagnosis and drug delivery vehicles, , high selectivity enabled by mass selection alone or in combination with structural separations prior to deposition plays a key role in developing an understanding at the molecular level. In combination with rapidly advancing ultrahigh-resolution imaging technologies (i.e., cryo-EM, low-energy electron holography, scanning probe microscopy, and scanning tunneling microscopy) ISL has recently been shown as an emergent approach to enable the characterization of molecular structures at the single-molecule level. For example, ISL was used to create a high-purity sample by mass-selecting for cryo-EM imaging of biomolecules as it allows for separation from aggregates, fragments, and molecules with altered structures, which are commonly produced in the conventional cryo-EM sample preparation process.…”
Section: Introductionmentioning
confidence: 99%
“…Already, direct combination of native MS and various analysis methods revealed retention of globular shape, and biological activity of proteins and viruses. [32][33][34][35] More recently, improved workflows using cryo-EM, negative stain transmission electron microscopy (TEM), or low-energy electron holography have demonstrated that protein complexes retain their overall shape at a resolution in the nanometer range. [35][36][37][38][39][40] However, in the absence of a method that provides structures of proteins at the level of side-chain resolution, the extent to which the solution structure is retained in the native ESIBD process has remained unclear.…”
mentioning
confidence: 99%